Implementing Project-Based Experiential Learning in Post-Graduate Studies in Greece: A Case Study - Karageorgou, Elissavet; Konstantina, Koutrouba (European Journal of Social Science Education and Research, 2017)
The present questionnaire-based study examines the outcomes of project-based learning procedures in Greek University postgraduate classes, where the project entitled “Traffic Signs” takes place. Master in Education students at Harokopio University provided relevant information by answering a set of close-ended questions specifically designed for the research. Data elaboration and statistical analysis were performed. The results of the study showed that, according to MEd students, the teachers’ role during the carrying-out of the project remains crucial, since s/he establishes the rules of communication, defines the objectives, simplifies the learning material and intervenes in a supportive way to strengthen students’ cognitive background and self-confidence, to overcome setbacks and facilitate constructive cooperation. The research also showed that as long as projects’ implementation during postgraduate studies are well-designed, attractive and demanding regarding high-ranked cognitive and socio-affective abilities, they meet satisfactorily students’ academic needs and expectations and refresh, deepen and expand the positive outcomes of the learning procedure even in scientific domains where very often University teachers tend to avoid the use of more innovative teaching methods.